A cavernous malformation associated with an acute subdural hematoma: case report and literature review - Dramane Cissé; Daniel Yamba Yamba; Mohammed El Ghabouch; Muhindo Dominique; Oualid Mohammed Hmamouche; Marouane Hammoud; Faycal Lakhdar; Mohammed Benzagmout; Khalid Chakour; Mohammed El Faiz Chaoui (Egyptian Journal of Neurosurgery)
Abstract Background Acute subdural hematoma secondary to bleeding from a cavernous malformation is uncommon, and few cases are reported in the literature. Case description We describe the case of a 40-year-old woman who had no prior history of significant illness and successfully underwent surgery for the management of acute subdural hematoma related to a right frontal cortical cavernous malformation revealed by intracranial hypertensive syndrome, and impaired consciousness Glasgow Coma Scale (GCS) was 7. Both lesions were resected, and the patient was doing good with a GCS 15 after 3 months of follow-up. Conclusion It is quite rare for a cavernous malformation to manifest as an acute subdural hemorrhage. When making a differential diagnosis for spontaneous acute subdural hemorrhage, cavernous malformation should be considered, and surgical resection is doable.